Association between obesity and a prothrombotic state: the Framingham Offspring Study - Rosito, Guido A.; D’Agostino, Ralph B.; Massaro, Joseph; Lipinska, Izabella; Mittleman, Murray A.; Sutherland, Patrice; Wilson, Peter W. F.; Levy, Daniel; Muller, James E.; Tofler, Geoffrey H. (Thrombosis and Haemostasis, 2004)
Although obesity is associated with increased cardiovascular risk, the mechanism has not been fully explained. Since thrombosis is a critical component of cardiovascular disease, we examined the relationship between obesity and hemostatic factors. We studied 3230 subjects (55% females, mean age 54 years) without a history of cardiovascular disease in cycle 5 of the Framingham Offspring Study. Obesity was assessed by body mass index and waist-to-hip ratio. Fasting blood samples were obtained for fibrinogen, plasminogen activator inhibitor (PAI-1) antigen, tissue plasminogen activator (tPA) antigen, factor VII antigen, von Willebrand factor (VWF), and plasma viscosity. Body mass index was directly associated with fibrinogen, factor VII, PAI-1 and tPA antigen in both men and women (p<0.001) and with VWF and viscosity in women. Similar associations were present between waist-to-hip ratio and the hemostatic factors. With minor exceptions for VWF and viscosity, all associations persisted after controlling for age, smoking, total and HDL cholesterol, triglycerides, glucose level, blood pressure, and use of antihypertensive medication. The association between increased body mass index and waist-to-hip ratio and prothrombotic factors and impaired fibrinolysis suggests that obesity is a risk factor whose effect is mediated in part by a prothrombotic state.
Keywords: Obesity; thrombosis; cardiovascular disease